2021
DOI: 10.1108/jmtm-08-2020-0324
|View full text |Cite
|
Sign up to set email alerts
|

Demand-pull vs supply-push strategy: the effects of organizational structure on supply chain integration and response capabilities

Abstract: PurposeRapid response is often the cornerstone of success in many industries, especially manufacturing. In the authors’ opinion, organizational structure will also affect the construction of a fast-response supply chain system. The main purpose of this research examines whether different levels of organizational structure have different effects on the relationship between external integration and firm performance.Design/methodology/approachThis study applied questionnaires to collect data. This study collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Flynn et al. (2010) and Chiang and Huang (2021) claimed that (II) removes functional barriers and enables cooperation and sharing of knowledge and information between internal functional areas. Thus, it improves product and process designs, removes waste and redundancy and unifies objectives.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Flynn et al. (2010) and Chiang and Huang (2021) claimed that (II) removes functional barriers and enables cooperation and sharing of knowledge and information between internal functional areas. Thus, it improves product and process designs, removes waste and redundancy and unifies objectives.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies identified that (II) is critical to successfully meeting customer requirements at the lowest total system cost (Boon-itt and . Flynn et al (2010) and Chiang and Huang (2021) claimed that (II) removes functional barriers and enables cooperation and sharing of knowledge and information between internal functional areas. Thus, it improves product and process designs, removes waste and redundancy and unifies objectives.…”
Section: Firm Performancementioning
confidence: 99%
“…Technological development comes from innovation, which can be traced to either a customer's initial idea or a supplier's suggestions that differentiate the two strategies of technological development: supply-push and demand-pull [8]. The supply-push model means that a technology holder or a supplier initiates the technology transfer and then pushes technology toward the market.…”
Section: Supply-demand Aspects In Technological Developmentmentioning
confidence: 99%
“…Indeed, managers perceive organizational effectiveness as an important outcome and variable proxy for organizational performance. In addition, organizational effectiveness is perceived as an ongoing essential function of the fit between organizational factors like structure, process, and external environments (Chiang and Huang, 2021). In this way, organizational effectiveness helps managers to assess how an organization is achieving its goals and uses its resources most effectively to continuously adapt effectively to its external environment.…”
Section: Introductionmentioning
confidence: 99%